Effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers on All-Cause Mortality and Renal Outcomes in Patients with Diabetes and Albuminuria: a Systematic Review and Meta-Analysis - Wang, Kanran; Hu, Jinbo; Luo, Ting; Wang, Yue; Yang, Shumin; Qing, Hua; Cheng, Qingfeng; Li, Qifu (Kidney & blood pressure research, 2018)
Background/Aims: Whether angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARB) could benefit patients with diabetes and albuminuria remains controversial. A systematic review and meta-analysis were conducted to answer this question by comparing ACE inhibitors or ARB with placebo among these patients. Methods: In this meta-analysis, electronic data sources (Medline, the Cochrane Collaboration, and EMBASE) were searched. Randomized controlled trials (RCTs) comparing ACE inhibitors or ARB with placebo in subjects with diabetes and albuminuria (defined as urinary albumin-to-creatinine ratio, UACR≥30mg/g Cr) were included. Outcomes parameters were all-cause mortality, end stage renal disease (ESRD), doubling of serum creatinine levels, and cardiovascular events (CV). Results: Twenty-six RCTs (including 20 for ACE inhibitors and 6 for ARB) were included, comprising 10378 participants with diabetes and albuminuria. Compared to placebo, treatment with ACE inhibitors or ARBs did not reduce all-cause mortality or CV. For renal outcomes, ARBs significantly reduced the risk of ESRD by 23% (odds ratio 0.77, 95%CI 0.65-0.92), while ACE inhibitors were not associated with a decreased risk of ESRD (0.69, 0.43-1.10). Both ACE inhibitors and ARBs reduced the risk of doubling of the serum creatinine level (0.60, 0.39-0.91 for ACE inhibitors; 0.75, 0.64-0.88 for ARBs), and subgroup analyses for patients with macroalbuminuria or microalbuminuria showed similar results. Conclusion: In patients with diabetes and albuminuria, ARBs reduced risks of ESRD and doubling of the serum creatinine level. ACE inhibitors and ARBs failed to reduce all-cause mortality and CV. Based on the renoprotective effects, ARBs may be preferred for diabetic patients with albuminuria.